Complementarity of formal and informal actors and their networks in support of vulnerable populations in informal settlements: Governance diaries approach - Chumo, Ivy; Kabaria, Caroline; Shankland, Alex; Igonya, Emmy; Mberu, Blessing (Frontiers in Public Health, 2023)
Introduction Beyond several interests and speculations on the relationship between formal and informal actors and their networks in support of vulnerable populations, most studies do not conclusively establish whether the two types of support are substitutes or complements. While informal care and formal care may be substitutes in general, they are complements among the vulnerable groups. Despite how some studies have described complementarity, further insights on the synergy between formal and informal actors and networks are needed to pinpoint how to maximize policy and interventions to alleviate the challenges facing vulnerable groups in informal settlements. Methods We conducted an ethnography using governance diaries with 24 participants in Korogocho and Viwandani informal settlements in Nairobi, Kenya. The governance diaries approach involved conducting bi-weekly governance in-depth interviews (IDIs) with study participants for 4 months, complemented with observations, reflections, participant diaries and informal discussions. We used framework analysis approach. Findings Informal actors identified include family, neighbors, friends, community groups and community members, and their direct networks. Formal actors on the other hand included government institutions, individuals and authorities that make policies and rules and their desired and possible networks. Both the formal and informal actors and their networks had complementary roles that were beneficial to the vulnerable populations living and working in informal settlements. The complementarities between formal and informal actors and networks in supporting vulnerable groups were portrayed in roles and responsibilities to the vulnerable groups; rules, regulations and governance in supporting vulnerable groups; knowledge, skills and dynamic workforces among formal and informal actors and their networks; information flow on health and wellbeing to the vulnerable populations; transition of actors in supporting vulnerable groups; availability, access and involvement of formal and informal actors and networks to support vulnerable groups. The complementarities allowed for maximum support of the vulnerable populations than otherwise. Conclusion We conclude that informal social support is needed regardless of the availability of formal social support. Moreover, a combination of formal and informal actors and related networks are essential to support vulnerable persons. Formal actors should establish, support, or maintain the informal actors and related networks through goodwill and sundry incentives as a vital dimension of building with local community structures and enhancing inclusion, participation and ownership of policy and program interventions by marginalized and vulnerable groups.